The female athlete triad - Nattiv, A.; Loucks, A. B.; Manore, M. M.; Sanborn, C. F.; Sundgot-Borgen, J.; Warren, M. P. (Medicine & Science in Sports & Exercise, 2007)
The female athlete triad (Triad) refers to the interrelationships among energy availability, menstrual function, and bone mineral density, which may have clinical manifestations including eating disorders, functional hypothalamic amenorrhea, and osteoporosis. With proper nutrition, these same relationships promote robust health. Athletes are distributed along a spectrum between health and disease, and those at the pathological end may not exhibit all these clinical conditions simultaneously. Energy availability is defined as dietary energy intake minus exercise energy expenditure. Low energy availability appears to be the factor that impairs reproductive and skeletal health in the Triad, and it may be inadvertent, intentional, or psychopathological. Most effects appear to occur below an energy availability of 30 kcal·kg-1 of fat-free mass per day. Restrictive eating behaviors practiced by girls and women in sports or physical activities that emphasize leanness are of special concern. For prevention and early intervention, education of athletes, parents, coaches, trainers, judges, and administrators is a priority. Athletes should be assessed for the Triad at the preparticipation physical and/or annual health screening exam, and whenever an athlete presents with any of the Triad's clinical conditions. Sport administrators should also consider rule changes to discourage unhealthy weight loss practices. A multidisciplinary treatment team should include a physician or other health-care professional, a registered dietitian, and, for athletes with eating disorders, a mental health practitioner. Additional valuable team members may include a certified athletic trainer, an exercise physiologist, and the athlete's coach, parents and other family members. The first aim of treatment for any Triad component is to increase energy availability by increasing energy intake and/or reducing exercise energy expenditure. Nutrition counseling and monitoring are sufficient interventions for many athletes, but eating disorders warrant psychotherapy. Athletes with eating disorders should be required to meet established criteria to continue exercising, and their training and competition may need to be modified. No pharmacological agent adequately restores bone loss or corrects metabolic abnormalities that impair health and performance in athletes with functional hypothalamic amenorrhea.